English language acquisition of first graders using the Whole Language approach: Whole Language - Cáceres Amaya, Heidy Andrea; López Díaz, Luz Dary; Beltrán Osorio, Mary Nelly (Rastros Rostros, 2002)
The acquisition of the English language by children in elementary school has been considered one of the fundamental bases that corresponds to a prospective vision of the XXI century; that a high percentage of Colombians should have access to the knowledge of a foreign language, mainly the most used international language: "English".